Coordinated operation of wind turbines and flywheel storage for primary frequency control support. (June 2015) - Díaz-González, Francisco; Hau, Melanie; Sumper, Andreas; Gomis-Bellmunt, Oriol
Highlights: Wind turbines have to be derated while participating in frequency control tasks. They improve nadir and steady state frequency level after a frequency disturbance. Flywheels reduce the need of derating wind turbines maximizing wind park output. Abstract: This work assesses the participation of wind power plants in primary frequency control support. To participate in frequency control-related tasks, the wind power plants have to maintain a certain level of power reserves. In this article, the wind power plant is equipped with a flywheel-based storage system to fulfil the power reserve requirements set by the network operator. The article focuses on two main aspects: the definition of the control strategy to derate the wind turbines to provide a part of the required power reserves; and the coordinated regulation of the power reserves of the wind turbines and the flywheels while participating in primary frequency control. This coordinated regulation enables the wind power plant to maintain the net level of power reserves set by the network operator while alleviating the need of deloading the wind turbines. The performance of the proposed control schemes are shown by simulation.